The effect of deadlines on cancer screening completion: a randomized controlled trial - Alicea Lieberman (Nature Portfolio, 2021)
Abstract Cancer is the second leading cause of death in the United States. Although screening facilitates prevention and early detection and is one of the most effective approaches to reducing cancer mortality, participation is low—particularly among underserved populations. In a large, preregistered field experiment (n = 7711), we tested whether deadlines—both with and without monetary incentives tied to them—increase colorectal cancer (CRC) screening. We found that all screening invitations with an imposed deadline increased completion, ranging from 2.5% to 7.3% relative to control (ps < .004). Most importantly, individuals who received a short deadline with no incentive were as likely to complete screening (9.7%) as those whose invitation included a deadline coupled with either a small (9.1%) or large declining financial incentive (12.0%; ps = .57 and .04, respectively). These results suggest that merely imposing deadlines—especially short ones—can significantly increase CRC screening completion, and may also have implications for other forms of cancer screening.